The Influence of Product Quality, Price, and Sales Promotion on Cassava Tape Purchase Decisions - Nyadia Ofianti; Misti Hariasih (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to examine the effect of Product Quality, Price, and Sales Promotion on Cassava Tape Purchase Decisions in Wonosari Village. In this study using quantitative methods. The total sample taken in this study was 100 respondents from Cassava Tape customers in Wonosari Village. . Data collection techniques using questionnaires. Data analysis in this study includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, linearity test, auto correlation test, multiple linear regression analysis, T test, multiple correlation coefficient (R) and coefficient of determination (R2). With the SPSS 22 (Statistical Package for the Social Sciences) tool. The results of this study prove that product quality affects purchasing decisions, price affects purchasing decisions, sales promotions affect purchasing decisions and product quality, price and sales promotions simultaneously affect purchasing decisions of Cassava Tape in Wonosari Village.